Pengabdian Mahasiswa dalam Meningkatkan Kepedulian Pemuda-Pemudi Gereja HKI Aek Raso Terhadap Kebersihan dan Kesehatan Lingkungan Gereja - Masrany Banjarnahor; Lili Aseka Simanjuntak; Chelshe Hutabarat; Delfitri Lubis; Diana Martini Situmeang (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
This student service activity aims to increase awareness of the young people of the HKI Aek Raso Church regarding the cleanliness and health of the church environment through a participatory approach. The main problem raised was the young generation's low awareness of the importance of keeping places of worship clean. Students from the Christian Education Management and Christian Religious Education Study Program at IAKN Tarutung actively involve youth in mutual cooperation activities, reflective discussions, and the preparation of routine cleaning schedules. This approach does not only focus on physical actions, but also character and theological education which emphasizes that cleanliness is part of the testimony of faith. The results of the service show an increase in youth initiative and responsibility in protecting the church environment. Apart from creating positive behavioral changes, this activity also strengthens social relations between congregations. It can be concluded that participatory based service is effective in forming a culture of sustainable hygiene care and strengthening the spirituality of the church community